A Rare Case of Large Hydatidiform Mole Mimicking a Term Pregnancy - Shrestha, A.; Bastakoti, R.; Pandey, N.; Poudel, R.; Ranjit, S.; Makaju, R. (Kathmandu University Medical Journal, 2022)
Molar pregnancy is a type of abnormal pregnancy that usually presents with amenorrhea, vaginal bleeding and elevated serum ß-hCG levels. We report a rare case of complete hydatidiform mole occurring in a 46-year-old P2L2 lady who presented with a term size uterus and elevated serum ß-hCG level (> 15,00,000 per deciliter, anemia (hemoglobin: 8.1 g/dL), difficulty in breathing and minimal vaginal bleeding. During the course of her evaluation, she had profuse vaginal bleeding, she underwent suction and evacuation, but bleeding was not controlled despite measures to control it. She was given uterotonics and antifibrinolytic agents and uterine artery ligation. But was proceeded with emergency hysterectomy for uncontrolled hemorrhage. The content of suction and evacuation was vesicles with blood clots and histopathology was reported as complete hydatidiform mole. The patient received a total of 4 units of packed red blood cells. She was discharged from hospital on 5th postoperative day and was followed up serial serum ß-hCG level. Therefore, complete mole can present with enlarged uterus, vaginal bleeding and anemia. It is also important to note that intractable bleeding following suction and evacuation not being controlled with uterotonics and antifibrinolytic agents and uterine artery ligation may require hysterectomy to save the patient’s life.